The Influence Of The Work Environment On Employee Performance at MSMEs Markets in Kertasari Village - Caniago, Aspizain (International Publisher, 2023)
The purpose of this study was to find out how the work environment influences the performance of employees who work for MSMEs in the area of Kertasari Village, Bandung Regency. The research method used in this study is to use quantitative methods by processing data using the SPSS program. The research sample was taken using a random sampling technique which was calculated using the slovin formula, which consisted of 88 samples. The results of this study explain that the physical and non-physical work environment has a positive and significant effect on the performance of employees at MSMEs in Kertasari Village. The value of the influence of the work environment on employee performance is 69.4%.